PENGGUNAAN SMART APP CREATOR (SAC) SEBAGAI PERANGKAT PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA INOVATIF - Arifin, Almukarramah (Universitas Bina Taruna Gorontalo, 2023)
The limited use of media in mathematics learning becomes one of the reasons we develop this research. Therefore, this research aim is to produce learning media in the form of mobile applications on Android or smartphones using Smart App Creator (SAC). As subject of research, students at SMP Negeri 1 Pinogaluman in grades VIIA and VIIB was carried out. The method used in this research is Research and Development (R&D) with modifications to the development stages of the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The feasibility of learning media is seen from three aspects, namely validity, practicality and effectiveness. Data collection techniques use interview instruments, observation, expert validation questionnaires, questionnaires and student responses, and test results. The product trial was conducted in two stages, namely a small-scale trial with research subjects of 5 students of class VIIB students and a large-scale trial with research subjects of 46 students of class VIIA and VIIB. The validity criteria for innovative learning media were obtained from the assessment of media experts and material experts with average scores of 4.30 and 4.40 (very feasible category). The product was given a practical value based on student responses with an average score of 91.53%, and an average teacher response of 94.49%. Innovative learning media is also considered effective based on test results with a one group pretest and posttest experimental design with an average pretest score of 54.57 and an average posttest score of 82.83